Panoramic landscape of orchards in Santa Clara Valley - Giroux, Eugene G. (photographer):::Creator::::::::::::
Panoramic landscape of orchards, water towers, houses, and barns spread across the Santa Clara Valley. In the center and center left of the photograph two relatively large houses are surrounded by orchards, both have water towers, and the house on the left has a windmill that shares a platform with the water tower. Many of the orchards appear to be blooming, so it is likely this photograph was created in the spring of 1923.